EFFECT OF INBREEDING ON THE LITTER TRAITS OF LARGE WHITE YORKSHIRE SOWS - M. Vasundara Devi; M.R. Jayashankar (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Data relating to 130 sows, 19 boars from 400 farrrowings spread over a period from 1984 to 1992 were utilized to study genetic and non-genetic effects in variation of litter size and weight at birth and at weaning. The overall mean litter size at birth (LSB)was 6.83 ± 0.13 piglets. The effects of period, season of farrowings and inbreeding on litter size at birth were not significant (P>0.05).The overall least squares mean of litter size at weaning(LWW) was 4.83 ± 0.12 and was significantly (Pd”0.05) affected by in breeding. Litter weight at birth (LWB) had a least square mean of 7.81 ± .16 kg and it was significantly (Pd”0.05) affected by period of farrowing. The mean LWB of non-inbred sows was 8.22 ± 0.19kg and that of inbred sows was7.41 ± 0.29 kg. The overall least squares mean for litter weight at weaning (LWW) was 39.36 ± 1.25 kg and inbreeding of sow exerted significant effect on LWW. The LWB and LWW were significantly affected by period of farrowing. The litter size at birth and at weaning and litter weight at birth and at weaning was not significantly affected by season of birth. The heritability estimates of litter size at birth and litter size at weaning were 0.096 ± 0.09 and 0.816 ± 0.27 respectively. The corresponding heritability values for LWB and LWW were 0.41 ± 0.18 and 0.53 ± 0.21 respectively.